Different strategies for sports injury prevention in an America`s Cup yachting crew - Hadala, M.; Barrios, C. (Archivos de medicina del deporte, 2008)
Preparation and training of an America`s Cup yacht-race crew need a time period which oscillates between 2 and 4 years. Most of the time is spent in base training, physical preparation and conditioning, boat reparations, sessions have important repercussions in the physical condition of sailors. The highest incidence (> 2/3 of injuries) is mainly observed in a specifi c group of athletes with high physical-work intensity (grinders, bowmen, and mastmen). Methods: A prospective physiotherapy intervention study during competition periods over three seasons was conducted on an America`s Cup Yachting-Race Crew of 30 professional sailors. In the 2 fi rst acts (2004), athletes did not receive any preventive physiotherapy. In the 2 acts celebrated in 2005, preventive intervention (phase I) consisted of stretching exercises prior to the yacht race and preventative taping. During the 4 acts corresponding to the 2006 season, the physiotherapy program was implemented adding articular mobilization before competition, ice-baths after competition, and kinesiotaping (phase II). In the last act and the Luis Vuitton Cup (2007), a recovery program with `core stability` exercises, post-competition stretching exercises, and 12 hours of compressive clothing were added (phase III). Results: In the pre-intervention phase (2004), the rate of injured sailors/competition day was 1.66, decreasing to 0.60 in 2007 (phase III). The number of athletes with more than one injury was signifi cantly reduced from 53% (8 of 15) to 6.5% (2 of 12). In the pre-intervention period, mastmen, grinders, and bowmen showed a rate of 2.88 injuries/competition day. After phase III, this group only suffered 0.5 injuries/competition day. Conclusions: The implementation of a program of preventive physiotherapy decreased the risk of injuries suffered during competition by an America`s Cup yacht crew.